1996
DOI: 10.1097/00005373-199606000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Flail Chest

Abstract: Significant differences were found: TV decreased from control values to FC and from FC to FIP, but increased from FC to FEP. RR values increased from control to FC and from FC to FIP, but decreased from FC to FEP. MV values decreased from FC to FEP. TV, RR, and MV were not changed under oxygen administration. Hypoxemia or hypercapnia were not observed. It was concluded that FIP is deleterious for respiratory mechanics, whereas FEP improves ventilatory parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The isolated use of a myocutaneous flaps for reconstruction in human patients after extensive thoracic wall resection (≥3 ribs) did not result in postoperative deterioration in pulmonary function as assessed by forced expiratory volume measurements 13 . Experimental canine models of flail chest have demonstrated that breathing pattern and arterial blood gas measurements are unaffected by paradoxical respiratory movement of a large flail segment (4–5 ribs) 14–16 . This literature supports use of non‐rigid thoracic wall reconstruction.…”
Section: Discussionmentioning
confidence: 57%
“…The isolated use of a myocutaneous flaps for reconstruction in human patients after extensive thoracic wall resection (≥3 ribs) did not result in postoperative deterioration in pulmonary function as assessed by forced expiratory volume measurements 13 . Experimental canine models of flail chest have demonstrated that breathing pattern and arterial blood gas measurements are unaffected by paradoxical respiratory movement of a large flail segment (4–5 ribs) 14–16 . This literature supports use of non‐rigid thoracic wall reconstruction.…”
Section: Discussionmentioning
confidence: 57%
“…Meshes and mesh‐methylmethacrylate sandwiches are preferred for these reconstructions as the additional rigidity reduces paradoxical chest wall motion and resultant ventilatory compromise, and provides superior protection of intrathoracic organs and vessels 9–12,28 . However, the necessity for rigid chest wall reconstruction in dogs is questionable because paradoxical chest wall motion does not affect ventilatory function in either experimental models of traumatic flail chest or in clinical reports of chest wall reconstruction in dogs 14,29–31 …”
Section: Discussionmentioning
confidence: 99%
“…Respiratory complications are also rare in other studies of chest wall reconstruction in dogs. Paradoxical motion of the reconstructed chest wall has been reported in dogs, 8,14 but, in both experimental and clinical studies, paradoxical motion in the absence of underlying pulmonary trauma does not result in pulmonary hypofunction in dogs 14,29–31 . As a result, more rigid chest wall reconstruction techniques, like mesh‐methylmethacrylate sandwiches and rib replacement with spinal lubra plates, are probably unnecessary in dogs.…”
Section: Discussionmentioning
confidence: 99%